Pastoral letters during the Marcos-Aquino transition period. [article]. - Montiel, Cristina
The study content analyzed bishops' pastoral letters during the Marcos-Aquino transition period. It likewise ran a bishops' survey, asking the church leaders to evaluate the effects of their social messages. Common imageries mentioned in the letters referred to traditional biblical personages. The father was powerful but loving. Christ-Lord was depicted as an influential but pained social leader. The more fiery imageries often cited by Philippine underground movements (e.g.,The Exodus and the angry Jesus in the temple) were not dominant messages. Pastoral letters were primarily religious statements backed by strong moral commentaries on Philippine contemporary politics. The attitudes change explanation of the social function of church documents is put under fire by research findings. Documents with the least anti-Marcos effects were the ones perceived by the bishops to have garnered the highest agreement scores among the diocesan flock. Instead of attitude change, environmental change may have operated to explain the social effects of the letters. The bishops' statements may have stirred just enough controversy in the already unstable political situation to catapult the February 1986 peaceful revolution into its finis.